Natural law theory in ethics according to allameh tabatabaei - rahim dehqan; amir divani (اخلاق وحیانی)
Abstract: Tabatabai is one the defenders of traditional moral theory of natural law. He based his plan ethics on human capacities that exist naturally in humans and by this view offered a defensible explanation of traditional natural law theory in ethics. According to the general guiding principle of development, he has four basic steps to outline a system of ethics that we are talking about in this article. His first step is to analyze the needs of human nature, and in the second step, in order to meet the needs, desires and talents as inner codes or specific developmental. In the third step, end to all this desire determined, and the fourth step is to find the direction to the human nature. This article attempts to analyze these four steps in allameh tabatabaei,s view and have a survey on the traditional natural law theory. Key words: human nature, moral values, structure, rationality, Tabatabai.